Recenze a anotace 1_2007 (Romano džaniben, 2007)
Ľudovít Didi / Príbehy svätené vetromGejza Horváth / TrisprasRonald Lee / Learn Romani. Das-dúma RromanesVlado Oláh / Khamutno kamibenNina Pavelčíková / Romové v českých zemích v letech 1945–1989Jozef Ravasz / Identita Rómov na Žitnom ostroveYvonne Slee / Torn Away, ForeverJsme přeci lidé, ne? – We’re all people, no?Peter Vermeersch / The Romani Movement. Minority Politics and Ethnic Mobilisation in Contemporary EuropeWriters Festival India – 2006 (21-24 March 2006)